Porous Ti3SiC2 fabricated by mixed elemental powders reactive synthesis. Issue 4 (April 2015) - Liu, Xinli; Jiang, Yao; Zhang, Huibing; Yu, Linping; Kang, Jiangang; He, Yuehui
Abstract A novel porous material Ti3SiC2 is synthesized using reactive synthesis of mixed elemental powders. The synthesized porous Ti3SiC2 has high purity more than 99.0%. By adjusting the fabrication parameters, porous Ti3SiC2 can be synthesized with average pore diameters ranging from ∼200 nm to over ∼40 μm and open porosity ranging from ∼19.5% to ∼53.2%. The pore formation mechanism has been studied. Also, the synthesized porous Ti3SiC2 material presents promising mechanical properties. This novel porous material has the potential to replace the traditional inorganic porous material.